Health literacy and TB-related stigma among nurses in Jayapura, Papua: A cross-sectional study - Sinaga, Eva; Batticaca, Fransisca; Suyanto, Agnes Angelita (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Tuberculosis (TB) remains a significant global and national health concern. In Papua, the TB treatment success rate has yet to reach national targets. One of the key barriers to achieving this goal is the stigma surrounding TB patients. Purpose: To identify the relationship between TB-related health literacy and nurse stigma at Abepura Regional Hospital. Method: A quantitative correlational study was carried out between April and June 2024, involving 125 purposively selected nurses from Abepura Regional Hospital. Data collection was conducted using a TB literacy questionnaire and a TB-Related Stigma questionnaire. The data were analyzed using univariate analysis and the Chi-square test. Results: Most respondents were female, non-Papuan, in early or late adulthood, held a bachelor's degree, and had 5-20 years of work experience. The majority were civil servants without prior TB-related training and were assigned to the Emergency and Pulmonary Rooms. While most respondents demonstrated good TB-related literacy, nearly 40% exhibited stigma toward TB patients. No significant correlation was found between TB health literacy and nurses' stigma. Conclusion: Despite possessing sufficient TB knowledge, nurses still exhibited a high level of stigma toward TB patients. Enhancing awareness and understanding among nurses and the community is essential through health promotion initiatives and strengthening the role of community and religious leaders.